Intelligent information and database systems : 12th Asian Conference, ACIIDS 2020, Phuket, Thailand, March 23-26, 2020, Proceedings, Part I /: 12th Asian Conference, ACIIDS 2020, Phuket, Thailand, March 23-26, 2020, Proceedings, Part I. (2020) - Unknown
No abstract available